2019
DOI: 10.1007/s11845-019-02148-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk of drug interactions and prescription appropriateness in elderly patients

Abstract: Background:In Europe, adverse drug reactions and drug interactions are cause of considerable morbidity and mortality. In over 75s, hospital access due to adverse drug reactions can be as high as 1 in every 3. Aims:To assess the quality of the prescribed polytherapies in the territory, in terms of the risk of drug interactions and of prescription appropriateness, in over 75s.Methods: Randomly selected patients, over 75s, were analysed among the patients of 3 general practitioners. Their data were analysed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 18 publications
3
13
0
1
Order By: Relevance
“…Possible explanations for the increased prescription of PPIs could be the frequent use of antiplatelet drugs and self-medication with propionic acid derivatives. Our results regarding the high prevalence of PPIs, especially in the elderly, were in line with findings from other studies [19,20,[27][28][29], suggesting that there was considerable room for improvement regarding the chronic use of PPIs; rational deprescribing of this pharmacological group in selected patients might be a good first step to reduce the risk of adverse events and hospitalizations [30]. There were warnings about their increasing consumption worldwide in both primary and hospital care settings [31,32]: their prolonged use was related to the risk of many adverse events [33,34], so they should be used for specific indications at the minimum effective dose and during the shortest possible period [9,35].…”
Section: Discussionsupporting
confidence: 93%
“…Possible explanations for the increased prescription of PPIs could be the frequent use of antiplatelet drugs and self-medication with propionic acid derivatives. Our results regarding the high prevalence of PPIs, especially in the elderly, were in line with findings from other studies [19,20,[27][28][29], suggesting that there was considerable room for improvement regarding the chronic use of PPIs; rational deprescribing of this pharmacological group in selected patients might be a good first step to reduce the risk of adverse events and hospitalizations [30]. There were warnings about their increasing consumption worldwide in both primary and hospital care settings [31,32]: their prolonged use was related to the risk of many adverse events [33,34], so they should be used for specific indications at the minimum effective dose and during the shortest possible period [9,35].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we found adverse events in 45% of hospitalized patients (INTERCheck ® analysis reported a high class D score for > 80% of these patients). Our findings are consistent with a previous study in patients aged > 75 years that found hospital admission due to adverse drug reactions was as high as one in every three [18]. The cut-off for the number of drugs for the risk of incurring a serious or very serious interaction was found to be five [18]; the mean number of drugs was above eight in our patients.…”
Section: Strengths and Weakness Of The Studysupporting
confidence: 92%
“…Our findings are consistent with a previous study in patients aged > 75 years that found hospital admission due to adverse drug reactions was as high as one in every three [18]. The cut-off for the number of drugs for the risk of incurring a serious or very serious interaction was found to be five [18]; the mean number of drugs was above eight in our patients. It is noteworthy that class D must be considered a contraindicated association between drugs, that should be discontinued or avoided.…”
Section: Strengths and Weakness Of The Studysupporting
confidence: 92%
“…Regardless of SARS-CoV-2 infection, aging and co-morbidities are well recognised independent drivers of the development of drug–drug interactions (DDIs) [ 4 6 ]. Aging is associated with physiological changes that significantly affect the pharmacokinetics and pharmacodynamics of various drugs, thus increasing the risk of inappropriate dosing and the development of drug-related toxicity [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%